THE INFLUENCE OF WORK LIFE BALANCE ON TURNOVER INTENTION WITH JOB ENGAGEMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AS INTERVENING VARIABLES - Amelia, Nur; Nugroho, Sidiq Permono (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2024)
The purpose of this research is to analyze the influence of work-life balance mediated with job engagement and organizational citizenship behavior on turnover intention. This research uses quantitative methods. The population in this study is all married female workers in the city of Surakarta. Later samples will be taken that can be generalized to represent the existing population. The sample is part of the number and characteristics of the population. Determining the sample size for this research used the Malhotra formula with the formula for the number of questions multiplied by six (6), so the number of respondents is 144 respondents. The sample determination in this research was carried out using purposive sampling. This research uses primary data collection techniques using interviews assisted by questionnaires. This research also uses the help of the Smart-PLS (Partial Least Square) approach data analysis application. From the results of the analysis that has been carried out, this research can be concluded as follows: Work-life balance has a significant positive effect on turnover intention so that the first hypothesis is supported. Work-life balance has a significant positive effect on job engagement so that the second hypothesis is supported. Work-life balance has a significant positive effect on organizational citizenship behavior so that the third hypothesis is supported. Job engagement has a significant negative effect on turnover intention so that the fourth hypothesis is not supported. Organizational citizenship behavior has a significant negative effect on turnover intention so that the fifth hypothesis is not supported. Work-life balance has a significant negative effect on turnover intention, mediated by job engagement, so the sixth hypothesis is not supported. Work-life balance has a significant negative effect on turnover intention, mediated by organizational citizenship behavior, so the sixth hypothesis is not supported.